2022
DOI: 10.1155/2022/6267720
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effect of Sufentanil on Myocardial Ischemia-Reperfusion Injury in Rats by Inhibiting Endoplasmic Reticulum Stress

Abstract: Objective. Sufentanil is the most common drug in clinical practice for the treatment of ischemic heart disease. This study is to investigate the protective mechanism of sufentanil on rat myocardial ischemia-reperfusion (I/R) injury. Methods. A rat I/R model was established by ligating the left anterior descending coronary artery. A total of 24 SD male rats were enrolled and divided randomly into the control group, I/R group, sufentanil group (SUF; 3 μg/kg), and diltiazem group (DLZ; 20 mg/kg; positive control)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Wu et al reported that sufentanil pretreatment could prevent myocardial I/R injury via the miR-125a/DRAM2 axis [ 37 ]. In I/R rats, sufentanil alleviates myocardial injury and plays a protective role by inhibiting oxidative stress, inflammatory response, and endoplasmic reticulum stress [ 14 ]. Therefore, further exploration to sufentanil is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wu et al reported that sufentanil pretreatment could prevent myocardial I/R injury via the miR-125a/DRAM2 axis [ 37 ]. In I/R rats, sufentanil alleviates myocardial injury and plays a protective role by inhibiting oxidative stress, inflammatory response, and endoplasmic reticulum stress [ 14 ]. Therefore, further exploration to sufentanil is required.…”
Section: Discussionmentioning
confidence: 99%
“…Studies reveal that sufentanil plays an important protective role in myocardial I/R injury [ 10 – 12 ]. Sufentanil has obvious protective effect on myocardial I/R injury in rats, and its mechanism may be related to activation of the ERK1/2 pathway and the inhibition of endoplasmic reticulum stress and oxidative stress [ 13 , 14 ]. In addition, a study by Li et al indicated a protective effect of sufentanil on skeletal muscle atrophy in septic patients [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increases in the levels of stress hormones, such as NE and E, indicate increased sympathetic nerve activity, and their entry into the bloodstream may cause vasoconstriction and trigger hemodynamic instability[ 26 ]. Ang Ⅱ activates the renin–angiotensin system and induces oxidative stress[ 27 ]. SOD exerts antioxidant effects by scavenging oxygen free radicals to reduce oxidative stress[ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%